Long-term Environmental Monitoring in Arctic Lakes and Ponds Using Diatoms and Other Biological Indicators - Smol, John; Douglas, Marianne (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary Long-term monitoring data are required to make effective environmental decisions. Unfortunately, such direct measurements are rarely available. Long-term data are especially sparse in arctic tundra regions, where logistic concerns often preclude the implementation of standard monitoring programs. However, paleolimnological techniques, such as the use of diatom assemblages preserved in dated lake and pond sediment profiles, can provide proxy data of past environmental changes.This paper summarizes some of the ways biological-based paleolimnological techniques can be used in arctic tundra environmentsto monitor environmental changes. Specific examples include studies of climatic change, airborne contaminants, and local disturbances.